The Bacterial Flagellar Motor: Insights Into Torque Generation, Rotational Switching, and Mechanosensing - Guo, Shuaiqi; Liu, Jun (Frontiers in Microbiology, 2022)
The flagellar motor is a bidirectional rotary nanomachine used by many bacteria to sense and move through environments of varying complexity. The bidirectional rotation of the motor is governed by interactions between the inner membrane-associated stator units and the C-ring in the cytoplasm. In this review, we take a structural biology perspective to discuss the distinct conformations of the stator and the C-ring that regulate bacterial motility by switching rotational direction between the clockwise (CW) and counterclockwise (CCW) senses. We further contextualize recent in-situ structural insights into the modulation of the stators by accessory proteins, such as FliL, to calibrate torque. The dynamic structural remodelling of the C-ring and stators as well as their association with signalling and accessory molecules provide a mechanistic basis for how bacteria adjust motility to sense, move through, and survive in specific niches both outside and within host cells and tissues.